Obtenção de derivados dos ácidos caurenoico e giberélico e avaliação do efeito fitotóxico e da atividade germinadora de alguns destes visando novos modelos de herbicidas - Rondinelle Gomes Pereira (2016)
This work shows the preparation of derivatives from kaurenoic acid (1), grandiflorenic acid (2) and gibberellic acid (GA3). The compounds obtained from kaurenoic acid were: 13 monoamides (3-16), seven derived from diamines and six derived from monoamines; one diamine (16), one hydrogenation product (17) and one monamide from such product (20), one amine (19), two alcohols (23 and 25) and two butenolides (28 and 29). One diol (24) was obtained from the grandiflorenic acid (2). The derivatives obtained from GA3 were one butenolide (30) and three esters (31-33). It is important to say that 15 compounds are described for the first time in this work. The phytotoxicity activity on weeds was evalueted for 3-16, 19 and 20, showing significant results of germination and growth inhibition. The compound 9, one of the most active, was chosen to evaluate the reproducibility of inhibitory effects in the greenhouse and its behavior in soil, in adsorption and desorption tests. The inducer activity of germination of parasitic plants was measured for 23-25 and 28-33. The derivatives 28-30, which have a characteristic butenolide ring from estrigolactones, showed higher activity, suggesting potential use in the development of substances with use in control of parasitic plants. The results obtained in this work support the potential use of kaurane derivatives in development of herbicides.